The Initial and Residual Value of Phosphorus from Apatite Rock Phosphates and Superphosphates as Measured by 32p Dilution Technique - Abdul Rahman, Zaharah; Abdul Hamid, Sharifuddin (1990)
A pot trial using maize (Zea mays, L.) grown on an Ultisollabelled with 32p was carried out to evaluate the agronomic value of nine types of apatite rock phosphates and triple superphosphate. Results show that the effectiveness of tested rock phosphates is variable as compared to superphosphate, when measured at 30 days after planting. However, these rock phosphates were three to five times more effective than triple superphosphate in the second cropping.